Non-polynomial fractional spline method for solving Fredholm integral equations - Jaza, Rahel; Hamasalh, Faraidun (Journal of Innovative Applied Mathematics and Computational Sciences, 2022)
A new type of non-polynomial fractional spline function for approximating solutions of Fredholm-integral equations has been presented. For this purpose, we used a new idea of fractional continuity conditions by using the Caputo fractional derivative and the Riemann Liouville fractional integration to generate fractional spline derivatives. Moreover, the convergence analysis is studied with proven theorems. The approach is also well-explained and supported by four computational numerical findings, which show that it is both accurate and simple to apply.